(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The present study was conducted to know the effect of schoolenvironment on the mental health and vocational interests of IX class students.The sample of the study was 200 students from government school (100students)and private schools (100 students) of Chandigarh. The researcher madeuse of the following tools for the present study: (i) School EnvironmentInventory (S.E.I.) by Mishra (2000), (ii) Mental Health Battery (M.H.B.) bySingh & Gupta, and (iii) Vocational Interest Record by Kulshreshtha (1977).The findings of the study revealed that the difference between the school environmentof government and private schools is not significant. Apart from this, itrevealed that the mental health of students of private and government schoolsis different from each other.